2014
DOI: 10.3168/jds.2014-8193
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Dairy consumption among middle-aged and elderly adults in Switzerland

Abstract: Different studies have shown that people are aware of the benefits of dairy products, but a sizeable part of the world's population still does not consume the recommended amount of dairy produce. The aims of the present research were to determine which dairy products are consumed by the middle-aged and elderly (50-81yr old) living in Switzerland and to explore why some of this population segment are actually reducing their consumption of dairy products. On average, older Swiss adults consumed 2.6 portions of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 8 publications
0
28
1
1
Order By: Relevance
“…The average number of servings found was 2.6, without significant differences between socioeconomic and demographic groups 34 . In a study based on data from the National Health and Nutrition Examination Survey (NHANES 2001(NHANES -2004, the authors found that more than half of the Americans consume than the minimum recommended amount of three daily servings of dairy products 32 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The average number of servings found was 2.6, without significant differences between socioeconomic and demographic groups 34 . In a study based on data from the National Health and Nutrition Examination Survey (NHANES 2001(NHANES -2004, the authors found that more than half of the Americans consume than the minimum recommended amount of three daily servings of dairy products 32 .…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, we estimated the prevalence of dairy product consumers (%) as well as the amounts consumed, always looking at the overall product category and 4 subgroups. Previous studies also evaluated the intake of dairy products in different populations, using distinct methods 10,25,[31][32][33][34] . Regardless of methodological differences, all this studies, including the present study point to the low consumption of dairy products.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two native speakers checked the three language-versions of the questionnaire. Participants answered a total of 50 questions regarding health and nutrition [26], milk and milk product consumption [27,28], meat and meat product consumption and socio-demographic variables. The present paper focuses on factors predicting consumption frequency of meat and meat products, and on motives underlying consumption avoidance or low consumption.…”
Section: Methodsmentioning
confidence: 99%
“…All transformations emanate from once a week = 1 portion. We made conservative choices for the transformation of portions per week into values and have chosen this approach to be conform to previous investigations [26,27]. …”
Section: Methodsmentioning
confidence: 99%
“…Elderly people tend to have a better compliance than younger, except for the consumption of dairy products [28][29][30] . This low consumption of dairy products might be related to the avoidance of full-fat dairy products due to high blood lipid levels or to increased intolerance to lactose 29 . Elderly participants were also more likely to be "new", "former" and "full" compliers to at least three guidelines recommendations than younger participants.…”
Section: Determinants Of Change In Compliance To Dietary Guidelinesmentioning
confidence: 99%